2017
DOI: 10.1139/bcb-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen inhibits mitochondrial membrane damage caused by disulfiram

Abstract: In this work, we studied the protective effects of tamoxifen (TAM) on disulfiram (Dis)-induced mitochondrial membrane insult. The results indicate that TAM circumvents the inner membrane leakiness manifested as Ca release, mitochondrial swelling, and collapse of the transmembrane electric gradient. Furthermore, it was found that TAM prevents inactivation of the mitochondrial enzyme aconitase and detachment of cytochrome c from the inner membrane. Interestingly, TAM also inhibited Dis-promoted generation of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the proteolytic fragments produced by cleavage of mutant ataxin-3 lead to nuclear translocation of ataxin-3 and cell death. In addition, it has been reported that disulfiram induces oxidative stress (Grosicka-Maciąg et al, 2010;Pavón et al, 2017). Oxidative stress has also been characterized as an inducer of nuclear ataxin-3 transport (Reina et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the proteolytic fragments produced by cleavage of mutant ataxin-3 lead to nuclear translocation of ataxin-3 and cell death. In addition, it has been reported that disulfiram induces oxidative stress (Grosicka-Maciąg et al, 2010;Pavón et al, 2017). Oxidative stress has also been characterized as an inducer of nuclear ataxin-3 transport (Reina et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The most adverse effect of disulfiram treatment is neurotoxicity, including neurofilamentous distal axonopathy, sensorimotor polyneuropathy and peripheral neuropathy in human patients and experimental animal models (Kulkarni et al, 2013;Stone et al, 2014). In addition, disulfiram can cause mitochondrial membrane damage (Pavón et al, 2017). Interestingly, one of the pathogenic mechanisms of SCA3 is mitochondrial dysfunction (Duarte-Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%